2016
DOI: 10.1016/j.ajog.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bariatric surgery on fetal growth restriction: experience of a perinatal and bariatric surgery center

Abstract: Malabsorptive bariatric surgery was associated with an increased risk of fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 28 publications
4
52
0
5
Order By: Relevance
“…Higher rates of SGA infants have been reported following biliopancreatic diversion compared to RYGB [100]. In a different study, IUGR was more common in women who underwent RYGB compared to gastric banding and sleeve gastrectomy [115]. However, a study by Facchiano et al [116] found no significant differences in outcomes between gastric banding and RYGB in terms of obstetric complications, gestational age or birth weight.…”
Section: Pregnancy After Bariatric Surgerymentioning
confidence: 88%
“…Higher rates of SGA infants have been reported following biliopancreatic diversion compared to RYGB [100]. In a different study, IUGR was more common in women who underwent RYGB compared to gastric banding and sleeve gastrectomy [115]. However, a study by Facchiano et al [116] found no significant differences in outcomes between gastric banding and RYGB in terms of obstetric complications, gestational age or birth weight.…”
Section: Pregnancy After Bariatric Surgerymentioning
confidence: 88%
“…Intrauterine growth restriction (IUGR) is increased by 2-3 fold after bariatric surgery (15, 38). In addition, pregnancies in women who had undergone procedures such as Roux-en-Y gastric bypass or RYGB, had a greater risk for SGA in comparison to weight loss procedures that such as LAPBAND, including VSG (11). Though many of the human studies report IUGR with RYGB and not LAPBAND, few studies have determined the occurrence of IUGR by type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The number of obese women in childbearing age undergoing bariatric surgery has risen significantly within the past years [1]. Although bariatric surgery is the most effective treatment for morbid obesity in diabetic patients [2,3], recent studies showed that women after surgery are at higher risk of perinatal complications such as preterm birth or delivering small-forgestational (SGA) infants [4][5][6][7]. In this context, we recently demonstrated a continuous decline in fetal growth throughout pregnancy after gastric bypass surgery, starting at the early second trimester [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we recently demonstrated a continuous decline in fetal growth throughout pregnancy after gastric bypass surgery, starting at the early second trimester [8]. Although the pathophysiologic mechanism beyond this observation remains unclear, it is believed that fetal growth delay is rather caused by nutrient deficiency and postprandial hypoglycemia (due to dumping syndrome) than by growth restriction due to placenta etiology or preeclampsia [5,9].…”
Section: Introductionmentioning
confidence: 99%